2009
DOI: 10.1213/ane.0b013e31818fc35b
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Perfusion Index as an Indicator for Intravascular Injection of Epinephrine-Containing Epidural Test Dose in Propofol-Anesthetized Adults

Abstract: PI is a reliable alternative to conventional hemodynamic criteria for detection of an intravascular injection of epidural test dose in propofol-anesthetized adult patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 20 publications
0
42
1
Order By: Relevance
“…The reliability of PI to detect vasoconstriction has been demonstrated by Mowafi et al in the study to detect intravascular injection of epinephrine containing epidural test dose. 12 In this study the cut off value of baseline PI for prediction of hypotension following spinal anaesthesia was chosen as 3.5.In the study by Toyoma et al they did regression analysis and ROC curve analysis and concluded that a baseline PI cut off point of 3.5 could be used to identify pregnant women at risk of hypotension following spinal anaesthesia based on the above study. 8 The baseline PI >3.5 and probability of hypotension were significantly correlating in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The reliability of PI to detect vasoconstriction has been demonstrated by Mowafi et al in the study to detect intravascular injection of epinephrine containing epidural test dose. 12 In this study the cut off value of baseline PI for prediction of hypotension following spinal anaesthesia was chosen as 3.5.In the study by Toyoma et al they did regression analysis and ROC curve analysis and concluded that a baseline PI cut off point of 3.5 could be used to identify pregnant women at risk of hypotension following spinal anaesthesia based on the above study. 8 The baseline PI >3.5 and probability of hypotension were significantly correlating in this study.…”
Section: Discussionmentioning
confidence: 99%
“…it is an indirect, noninvasive and continuous measure of peripheral perfusion [10]. Previous studies have demonstrated that an increase in PI is an early indicator that general [6][7][8] and epidural anesthesia [11,12] has initiated peripheral vasodilatation.…”
Section: Discussionmentioning
confidence: 99%
“…In patients of both groups, if any discomfort, agitation or unexpected movement occurred, incremental bolus of propofol (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) mg was given.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Also in propofol-anesthetized adult patients, the PI was found to be a reliable alternative to conventional hemodynamic criteria for detection of an intravascular injection of epidural test dose. 19 Furthermore, PI was shown to be a reliable and simple alternative to conventional hemodynamic criteria for detection of stress response to insertion of i-gel, laryngeal mask airway and endotracheal tube in adult patients. 20 In the neonatal acute care setting, a low PI has been shown to be an objective and accurate measure of acute illness.…”
Section: Discussionmentioning
confidence: 99%